DEVELOPMENT OF PROGRESSIVE FORMS AND WAYS TO STIMULATE INNOVATION IN MODERN CONDITIONS - E. Alekhina; V. Parakhina (Вестник Северо-Кавказского федерального университета)
The article substantiates the relevance of finding progressive forms and ways to stimulate innovation in modern conditions. The importance of the use ofprogressive forms and methods ofstimulating innovation in the economy of the country is determined. The author focuses on the study of progressive forms and ways to stimulate innovation, characterized the reasons for not high innovation activity of most modern enterprises. The results of the analysis of forms and methods of stimulation of innovative activity applied within the framework of already developed projects and programs are described. The conclusion is made about the importance of the chosen tools for stimulating innovation activity depending on a number of parameters such as the type of economic activity, the level of motivation of senior staff, the structure of the enterprise and other aspects.